IDENTITY CONSTRUCTION REFLECTED THROUGH NON-VERBAL BEHAVIORS IN PARASITE MOVIE - Sianturi, Yohana Zirah; Tetty, Morada (TRANSFORM: Journal of English Language Teaching and Learning, 2022)
The research discussed identityconstruction built in the movie of Parasite through the nonverbal behaviors aspect. The aims of this study were to find out the types of identity construction reflected through non-verbal behaviors, how the identity reflected in the movie, and to find out the reasons of the emergence of identity construction in the movie. The descriptive qualitative method is being used in this research, and the data were derived from the Parasite movie™s screenshot. The findings of the study showed that: (1) There are three identities found they are person identities, role identities, and social identities. (2) The identity construction reflected through non-verbal behaviors are object, accessories, smells/body odor. (3) The significance of identity construction emergence in the movie is to shows that every detail used in people daily can form an identity, and because movies are one of the products that people consume the most, then this becomes very helpful in showing the realities of real life.